Implementasi Kebijakan Publik tentang Model Pengurangan Resiko Bencana dengan Pendekatan Pada Masyarakat Dalam Program Desa Tahan Bencana Di Daerah Istimewa Yogyakarta - Vibriza Juliswara; Rusman Rupinus Manik; Djuniawan Karnadjaja (Program Studi Pembangunan Masyarakat Desa (D3), 2022)
The increase in disasters in Indonesia from year to year worries the government and people in disaster-prone areas. For this reason, BNPB (National Disaster Management Agency) launched a community-based program, namely Destana (Disaster Resistant Village) which is implemented by the Regional Disaster Management Agency (BPBD) Special Region of Yogyakarta through public policy. This research focuses on the implementation of the Destana program. The data collection methods were conducted through interviews and narrative question and answer. The results of the research, BPBD DIY has succeeded in forming 243 Destana which are spread across four disctricts and one city of DIY, the community is involved in identifying potential disasters in their area, taking preventive measures, being aware of the impact of disasters and how to deal with them, education, and forming volunteer groups. Conclusion, the Destana program in DIY was implemented by increasing public awareness, the ability to deal with disaster threats and being proactive, participatory and organized as an indication that the implementation of public policy in DIY in reducing disaster risk can be used as a model to reduce the impact of disasters in other regions